On the role of space–valence congruency in bilingual orientational metaphor processing - Tomasz Dyrmo; Katarzyna Jankowiak; Patrycja Kakuba (Language and Cognition)
Metaphor processing has been mostly researched using the space–valence paradigm, where participants respond to either space–valence congruent or incongruent stimuli. Little attention has, however, been devoted to the role of valence–space associations in bilingual orientational metaphor comprehension. Here, we employed a reaction time method and tested Polish (L1) – English (L2) highly proficient bilinguals, who performed a metaphoricity judgment task to L1 and L2 conceptual metaphoric sentences that were either valence–space congruent (BAD IS DOWN and GOOD IS UP) or incongruent (BAD IS UP and GOOD IS DOWN). The results showed a valence effect, where negatively valenced sentences were evaluated more accurately than positively valenced stimuli. We also found an interaction between valence, congruency and language, such that in both L1 and L2, negatively and positively valenced congruent metaphors were easier and faster to process than those violating the space–valence congruency. Altogether, this study provides a more embodied and experientially grounded approach to studying human cognition, lending credence to the automatic activation of primary metaphorical mappings in the human mind.